Advances in Network Electrophysiology Using Multi-Electrode Arrays - Taketani, Makoto; Baudry, Michel (Springer US : Imprint: Springer, 2006)
This book book is an attempt to review the recent progress in both electronics and computational tools developed to analyze the functional operations of large ensembles of neurons and to provide the readers with a sense of the applications made possible by these technological tools. While considerable progress has been made over the last decades in our understanding of electrophysiological processes at the single channel, single synapse, and single neuron levels, our understanding of electrophysiological processes at the neuronal network level is still in its infancy. This book includes: Technological overviews of multi-electrode arrays (MEAs) and related electronics and software, Applications of MEAs to study ensemble activity of dissociated cell cultures including cardiac myocytes, Applications of the technology for drug discovery using acute and cultured slices. Examples of studies directed at understanding the origins and functions of various rhythmic activities in neuronal ensembles.